Corneal morphological changes after small incision lenticule extraction for myopic anisometropia - Zhu, Lu; Ji, Yan; Yang, Xin; Lu, Xiaorong; Wu, Qiong; Wang, Qing; Xia, Jiuyi; Li, Meng; Hu, Ke; Wan, Wenjuan (Frontiers in Medicine, 2022)
Purpose: This research aims to study the corneal morphological changes in adult patients with myopic anisometropia after small incision lenticule extraction (SMILE) and the safety, efficacy, and predictability of clinical outcomes. Methods: This was a prospective cohort study. Patients with myopic anisometropia (refractive difference>2.0 diopters (D)) were included in this study who underwent SMILE at our hospital from September 2019 to March 2021. For the two eyes of each patient, the one with higher myopia was defined as group A, and the fellow eye was group B. The follow-up time points were set as one week, one month, three months, and six months after the surgery. The data collected were uncorrected and best-corrected distance visual acuity ((UDVA and CDVA), spherical equivalent (SE), efficacy and safety indexes, posterior corneal elevation (PCE), anterior and posterior corneal radius of curvature in the 3 mm area at the center of the thinnest point of the cornea (ARC and PRC), and higher-order aberrations (HOAs). Results: The study included 36 patients (72 eyes), and the mean age was 25.2±6.4 years. The preoperative SEs were -6.45±1.25 D in group A and -3.76±1.29 D in group B. Six months after surgery, the SEs in groups A and B were -0.09±0.50 D and 0.07±0.47 (P=0.059), respectively. The efficacy indexes were 1.06±0.16 in group A and 1.07±0.14 in group B (P=0.750). The safety indexes were 1.08±0.14 in group A and 1.12±0.15 in group B (P=0.173). The PCE was significantly reduced at six months after surgery in both groups (P<0.05). The ARC was significantly higher than before the surgery (P<0.05) in the two groups. The two groups showed significant increases in total HOAs, coma 90°, and spherical aberrations (P<0.05). Conclusions: SMILE is predictable, effective, and safe in correcting myopic anisometropia. The postoperative changes in HOAs are characteristic.